Mammalian dwarfins are phosphorylated in response to transforming growth factor beta and are implicated in control of cell growth. - Yingling, J M (1996)
The dwarfin protein family has been genetically implicated in transforming growth factor beta (TGF-beta)-like signaling pathways in Drosophila and Caenorhabditis elegans. To investigate the role of these proteins in mammalian signaling pathways, we have isolated and studied two murine dwarfins, dwarfin-A and dwarfin-C. Using antibodies against dwarfin-A and dwarfin-C, we show that these two dwarfins and an immunogenically related protein, presumably also a dwarfin, are phosphorylated in a time- and dose-dependent manner in response to TGF-beta. Bone morphogenetic protein 2, a TGF-beta superfamily ligand, induces phosphorylation of only the related dwarfin protein. Thus, TGF-beta superfamily members may use overlapping yet distinct dwarfins to mediate their intracellular signals. Furthermore, transient overexpression of either dwarfin-A or dwarfin-C causes growth arrest, implicating the dwarfins in growth regulation. This work provides strong biochemical and preliminary functional evidence that dwarfin-A and dwarfin-C represent prototypic members of a family of mammalian proteins that may serve as mediators of signaling pathways for TGF-beta superfamily members.